2018
DOI: 10.24198/pjd.vol30no1.16110
|View full text |Cite
|
Sign up to set email alerts
|

The effect of nanoparticles TiO2 on the flexural strength of acrylic resin denture plate

Abstract: Introduction: Acrylic resin is still the most commonly used denture base material due to its ideal properties. However, acrylic resin denture fractures are still considered a major unsolved problem thus the addition of nanoparticles as filler was performed to increase its mechanical properties. The purpose of this study was to discovered the effect of nanoparticles TiO2 on the flexural strength of acrylic resin denture plate. Method: This study used 27 heat-cured acrylic resin specimens sized 65 x 10 x 2.5 mm.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 10 publications
0
8
0
Order By: Relevance
“…The residual monomer represents as a plasticizer since it was capable to step inside among the polymer chains which occasion the separate chains turned into more tenuous and the attraction force among molecules minimizes so that the acrylic resin turns into more flexible but brittle during the flexural strength experiment. (18) Nazirkar et al informed a decrease in flexural strength amounts when contrast to the classic unmodified resin. The authors explained that the reinforced TiO2NPs act as an impurity and intervenes with the polymerization process.…”
Section: Resultsmentioning
confidence: 99%
“…The residual monomer represents as a plasticizer since it was capable to step inside among the polymer chains which occasion the separate chains turned into more tenuous and the attraction force among molecules minimizes so that the acrylic resin turns into more flexible but brittle during the flexural strength experiment. (18) Nazirkar et al informed a decrease in flexural strength amounts when contrast to the classic unmodified resin. The authors explained that the reinforced TiO2NPs act as an impurity and intervenes with the polymerization process.…”
Section: Resultsmentioning
confidence: 99%
“…39 In the current study, although the highest flexural strength value was seen in the group reinforced with 3 wt% TiO 2 , Tandra et al observed a decrease in the flexural strength values in 3 wt% TiO 2 groups compared to the traditional resin. 40 On the other hand, Ahmed et al determined the flexural strength by adding 1 wt% and 5 wt% TiO 2 nanoparticles to conventional and high strength heat-cured acrylic resin, they stated that the three-point bending value was significantly reduced by increasing the TiO 2 concentration in both acrylic resins. 41 Karci et al observed the reduced flexural strength value in groups to which 3 wt% and 5 wt% TiO 2 nanoparticles were added and stated that the non-homogeneous dispersion of the particles leads to agglomeration.…”
Section: Discussionmentioning
confidence: 99%
“…The authors stated that the introduction of reinforced TiO 2 NPs could interfere with the polymerisation process but they failed to explain the possible mechanism of this action. Tandra et al [ 42 ] observed that the formation of greater quantities of TiO 2 NPs agglomerates interfered with the polymerisation reaction. TiO 2 NPs additives at high concentrations also increased the amount of residual monomer by acting as a plasticiser [ 43 ].…”
Section: Discussionmentioning
confidence: 99%